Effects of Short-Day and Gibberellic Acid Treatments on Summer Vegetative Propagation of Napier Grass (Pennisetum purpureum Schumach) - Yasuyuki Ishii; Asuka Yamano; Sachiko Idota (International Journal of Agronomy)
The effects of short-day (SD) and gibberellic acid (GA3) treatments on promoting vegetative propagation during the summer were examined in Napier grass (Pennisetum purpureum Schumach). A dwarf variety of late heading type (DL) Napier grass was exposed to three SD treatments (5, 10, and 20 short days plus a spray of 400 ppm GA3 solution following each SD treatment, GASD) or no treatment (control). Additionally, then, a dwarf variety of early heading (DE) and the normal variety of Merkeron (ME) were exposed to 10 days of GA-SD treatment together with nontreated controls. For DL and DE, GA-SD treatments showed the following effects: 10-day GA-SD treatment increased significantly (P<0.05) the length of lateral tiller buds, maintained a high rooting percentage, and increased the diameter of the tiller buds. This resulted in a taller plant, one with enhanced tiller numbers, and thus a greater number of established nursery plants for the two dwarf varieties. In contrast, there was only a limited positive effect of the GA-SD treatments on the normal variety, ME. Thus, 10 days of GA-SD treatment was judged to be the most effective treatment for promoting lateral tiller bud elongation and early maturation in tiller buds for the two dwarf varieties of Napier grass.